Pengaruh Leverage, Total Asset Turnover Dan Ukuran Perusahaan Terhadap Harga Saham Dengan Deviden Payout Ratio Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2017-2021 - Fazharullah, Mhd.; Sani, Ahmad; Nurmadi, Ruswan (Universitas Labuhanbatu, 2024)
The purpose of this study was to test and analyze the effect of leverage, total asset turnover, company size on stock prices with the dividend payout ratio as an intervening variable. The approach used in this research is a quantitative approach. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The sample in this study used purposive sampling, amounting to 21 companies. Data collection techniques in this study using documentation techniques. Data analysis techniques in this study used path analysis using statistical analysis using Auter Model Analysis, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program.The results of this study prove that directly leverage, total asset turnover and dividend policy have no effect on stock prices, company size has an effect on stock prices, leverage, total asset turnover has no effect on dividend policy, dividend policy is not able to mediate the effect of leverage, total asset turnover and company size to stock price.